2017
DOI: 10.1539/joh.16-0123-fs
|View full text |Cite
|
Sign up to set email alerts
|

Health status assessment of workers during construction phase of highway rehabilitation projects around lahore, Pakistan

Abstract: Objective: The study focused on assessment of the health status of workers during construction phase of highway rehabilitation projects at six selected sites of N5 around Lahore, including Kala Shah Kaku, Muridke, Kamuki, Bhaipheru, Pattoki, and Okara.Methods: The study was based on multi-methods approach involving hazard identification through survey and checklist as well as a questionnaire for health status assessment and measurements of health parameters including peak expiratory flow rate (PEFR) and audiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…To sum up, the limited studies found in the literature offered by various researchers/organizations on beneficiary assessment for the road project. In Lahore, after the implementation of LRR, no studies of its impacts were conducted except a few, including Abrar et al (2014), which was about the health impact assessment study of the southern loop. Still, no study on its economic or other impacts has been found.…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, the limited studies found in the literature offered by various researchers/organizations on beneficiary assessment for the road project. In Lahore, after the implementation of LRR, no studies of its impacts were conducted except a few, including Abrar et al (2014), which was about the health impact assessment study of the southern loop. Still, no study on its economic or other impacts has been found.…”
Section: Introductionmentioning
confidence: 99%
“…2 A study conducted on 300 highway workers concluded that lack of safety measures from noise, vibrations, asphalt fumes, poor work postures and injuries are considered to be major health hazards . 3 Similarly, another study from 2016 to 2017 of 70 welders found 47% experienced eye injuries and 50% cuts and injuries, and other findings indicated that welders had a low level of awareness and few preventative measures were recommended . 4 A study on the index value of injured employees revealed that the financial implications amounted to over 32 000 Pakistani rupees per injured worker .…”
mentioning
confidence: 97%